Exploring the Vertical Design Charrette as an Alternative to Traditional Service-Learning - Stephanie Sickler; Amanda Gale (The University of Alabama, 2022)
This paper highlights a collaborative, intercollegiate vertical design charrette that illuminates the potential of short-term service opportunities. Interior design students from two major universities collaborated with a community partner over a 4-hour design charrette to produce preliminary design solutions for an expansion of the partner's residential community farm that houses adults with special needs. Student participants were at varying points in their college careers, and the vertical nature of the charrette experience facilitated extensive peer-to-peer learning. Little research to date has documented the potential of design charrettes as service opportunities. This experience challenges the notion of traditional service-learning as a sustained experience and posits that short-term experiences combined with diverse stakeholder groups can create equally valuable outcomes for both student learners and community partners. Further, including students of all levels in the design program led to organic, student-driven knowledge building throughout the charrette. In this way, students benefited not only from the service aspect of the charrette experience but also from the opportunity to collaborate with peers from another institution, resulting in increased agency over their own learning.